Adsorption of carbon dioxide on ammonia-treated carbon coated monolith - Marahel, Ehsan (2013)
Due to the greenhouse effect, the reduction and recovery technology of carbon dioxide has become an important research topic nowadays. In addition to the researches on the use of carbon dioxide as a reactant, the recovery and concentration of carbon dioxide from waste gas are the key issues. The adsorption method that is used to capture CO2, is in a packed-bed column. In this study, a monolithic column designed to separate and concentrate CO2 from He/CO2 mixture, was used to study the feasibility for recovery of CO2 from gaseous mixture. The surface properties of carbon-coated monolith were modified by N-containing group of ammonia aqueous and potassium hydroxide to increase CO2 adsorption and then compare it with untreated Carbon-Coated Monolith’s (CCM) capacity. BET, EDX, SEM, FT-IR, and Boehm titration methods were used to identify the physical and chemical properties of modified and un-treated CCM. The adsorption capacity and characteristics of carbon dioxide on carbon-coated monolith have been measured out in a variety of temperatures (303, 313, and 323 K), pressure (100,150, and 200 kPa), flow rate (15 to 480 mL/min), and variety of concentration (5 to 35%) of CO2 in feed. Modification by ammonia aqueous and potassium hydroxide as an N-containing method were treated to enhance the basicity of carbon surface. Different concentrations of ammonia were applied to introduce some functional groups such as (N-H) on surface so that it would increase adsorption capacity. Concentration of CO2 output from the carbon-coated monolith packed column is a function of time that was indicated by an analyzer. The adsorption capacity showed increase adsorption with increasing input flow rate, pressure,and concentration, and reduction of CO2 adsorption capacity with rising temperature up to 323K. Modified CCM (ACCM-75) showed an increased adsorption capacity of CO2 by around 12 % and PCCM showed an increase of almost 27 % compared to untreated CCM.The Deactivation Model (DM) derived using the analogy between the adsorption of CO2 and the deactivation of catalyst particles. Observed adsorption rate constants (Ks) and first-order deactivation rate constant (Kd) were obtained from the model. It was found that the DM describes experimental breakthrough curves very well. The isotherm was fitted well with the Toth and Langmuir equations.